Cover page (Discussion Papers, 1988)
The meeting organized by Polish and Hungarian social geographers had served for more than a decade the comparison of ways and problems of regional development and of efforts made in this field by the two countries. This volume contains the papers of the 6th Seminar on “Spatial organisation and regional development”. By virtue of the subject, papers can be divided into three major groups: one part focuses mainly on general issues of regional policy; another part highlights changes of regional structure of socio-economic services and investigates problems to be solved; while the third group aims to give a complex presentation of minor regions. The regional problems of services, or more generally the role of services in regional development of society was given particular attention during this conference. The volume was published by the Centre for Regional Studies, Hungarian Academy of Sciences.